2011
DOI: 10.1002/jctb.2668
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency bioethanol production from OPEFB using pilot pretreatment reactor

Abstract: BACKGROUND: Current ethanol production processes using crops such as corn and sugar cane are well established. However, the utilization of cheaper biomasses such as lignocellulose could make bioethanol more competitive with fossil fuels while avoiding the ethical concerns associated with using potential food resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Although, sonication time did not appear significant as an individual effect, but its interaction with acid concentration (AC) was significant to improve the sugar release from rice straw. Besides their non-significance, interaction, and quadratic terms were not omitted from the quadratic model as suggested in some studies (Chauhan and Gupta 2004;Han et al 2011a) because the quadratic and interaction terms (even non-significant) contribute to the response vector up to certain extent (Khalili et al 2011). Three-dimensional response surface plots were constructed to find out the optimum level of each factor with an objective to maximize the sugar yield.…”
Section: Resultsmentioning
confidence: 99%
“…Although, sonication time did not appear significant as an individual effect, but its interaction with acid concentration (AC) was significant to improve the sugar release from rice straw. Besides their non-significance, interaction, and quadratic terms were not omitted from the quadratic model as suggested in some studies (Chauhan and Gupta 2004;Han et al 2011a) because the quadratic and interaction terms (even non-significant) contribute to the response vector up to certain extent (Khalili et al 2011). Three-dimensional response surface plots were constructed to find out the optimum level of each factor with an objective to maximize the sugar yield.…”
Section: Resultsmentioning
confidence: 99%
“…However, it seems that alkali pretreatment is the most effective pretreatment method for oil palm biomass according to what is reported in the literature. Han and his colleagues investigated NaOH pretreatment of OPEFB for bioethanol production and a total glucose conversion rate (TGCR) of 86.37 % was obtained (Han et al 2011 ). Lignin degradation might contribute to the effectiveness of alkali pretreatment and H 2 O 2 posttreatment can further enhance such effects.…”
Section: Pretreatment Of Solid Oil Palm Biomassmentioning
confidence: 98%
“…Oil palm biomass pretreatment can be classifi ed into biological pretreatment, physical pretreatment, chemical (Syafwina et al 2002 ;Amin et al 2010 ). Chemical method is the most often used pretreatment method for oil palm biomass, such as two-stage dilute acid hydrolysis (Millati et al 2011 ), alkali pretreatment (Han et al 2011 ), sequential dilute acid and alkali pretreatment (Kim et al 2012 ), alkali and hydrogen peroxide pretreatment (Misson et al 2009 ), sequential alkali and phosphoric acid pretreatment (Kim et al 2012 ), aqueous ammonia (Jung et al 2011a ), and solvent digestion ). However, it seems that alkali pretreatment is the most effective pretreatment method for oil palm biomass according to what is reported in the literature.…”
Section: Pretreatment Of Solid Oil Palm Biomassmentioning
confidence: 99%
“…Hassan et al (2013) studied the pretreatment effects of steam assisted 5% acidic and alkaline pretreatments by using acetic acid as well as NaOH solutions and found that steam assisted acetic acid produced better results for enzymatic saccharification and sugar production enhanced to 62.36% xylose and 81.84% glucose. Han et al (2011) studied the effect of alkaline pretreatment and used concentrated NaOH (3M). They reported 85% total cellulose conversion by enzymatic saccharification.…”
Section: Figure 1-pretreatment Process Of Lignocellulosicmentioning
confidence: 99%